Model of mental health care in the Erundina administration (1989-1992) in the São Paulo City, São Paulo State, Brazil (Research, Society and Development, 2020)
This study aims to analyze the mental health care model implemented in the city of São Paulo in the Erundina management (1989-1992). Qualitative, descriptive exploratory research, theoretical methodological framework of thematic oral history based on the narratives of managers and professionals of the Mental Health Program of the city of São Paulo in the management described. The results indicated that the organization of network care of mental health services focused on the various levels of health care, focused on primary care, invested in the intersectoral and multiprofissional as never before, with a view to social reintegration and against the current manicomial model, built importants strategics bridges in the partnership between professional, family members and suffering subjects. It is considered that the São Paulo model was avant-garde, with changes in the way of seeing and doing care due to the organization of mental health care the commitment of professionals and inclusion of family members and subjects in suffering and integration of various sectors and public service.